Moderators of the response to deep TMS for smoking addiction - Gersner, Roman; Barnea-Ygael, Noam; Tendler, Aron (Frontiers in Psychiatry, 2023)
Introduction Deep repetitive transcranial magnetic stimulation (Deep TMSTM) was recently cleared by the FDA as a short-term treatment for smoking cessation. However, it is unknown which participants are more likely to benefit from the treatment. Methods We evaluated the data from the published randomized controlled trial of 262 participants 22-70 years old that led to the FDA clearance to characterize demographic and smoking history factors that moderate Deep TMS treatment efficacy. The current analysis included 75 completers in the active TMS group and 94 completers in the sham TMS group. Results We found that participants younger than 40 had four times the quit rate than those older than 40. Additionally, participants who quit following treatment smoked 10 years less than non-quitters. Moreover, Caucasian participants had two times the quit rate than African-American participants. Strikingly, participants with more than 12 years of education had 7 times the quit rate than participants with less education. Conclusions Three weeks of Deep TMS has a higher smoking addiction quit rate in participants who are younger, more educated, Caucasian and with less extensive smoking history. Participants who are older, with less education and more extensive smoking history may need a longer treatment course and/or combined treatment modalities. Potential reasons may be related to the challenges of inducing neuronal modifications in those with greater physical and psychological dependence. Further investigation is warranted.